Plasmonic nanostructures made by anodized aluminum oxide templates - Liusman, Cipto. (2013)
Plasmonic nanostructures, such as Au and Ag nanostructures, have become one of the most appealing and active research topics in nanotechnology, enabling many fundamental studies and applications in numerous scientific disciplines. By tailoring the size, shape, composition, and environment of plasmonic nanostructures, light can be controlled in many unique means. While the relatively simple, generally isotropic, and homogenous nanostructures have demonstrated some of plasmonic properties, the building structures with increased complexity and hierarchy will be necessary to realize the most useful nanoscale architectures. One of the methods for preparation of complex and intricate nanostructures is the electrochemical deposition in anodized aluminum oxide (AAO) template method with the key advantage of length and composition control.